Impact of the new definition for pulmonary hypertension in patients with lung disease: an analysis of the United Network for Organ Sharing database. (March 2021) - Nathan, Steven D.; Barnett, Scott D.; King, Christopher S.; Provencher, Steeve; Barbera, Joan A.; Pastre, Jean; Shlobin, Oksana A.; Seeger, Werner
The implications of the recent change in the definition of pulmonary hypertension on epidemiology and outcomes are not known. We sought to determine the percentage of patients with the two most common lung diseases that would be reclassified regarding the presence/absence of pulmonary hypertension with the revised definition. A query of the United Network for Organ Sharing database was performed. The percentage of patients meeting the current and previous definition of pulmonary hypertension was described. Outcomes of patients stratified by the current and previous definitions were compared. There were 15, 563 patients with right heart catheterization data analyzed. Pulmonary hypertension was more prevalent in both chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis under the new definition at 52.4% versus 82.4%, and 47.6% versus 73.6%, respectively. "Pre-capillary" pulmonary hypertension by the new definition was lower at 28.1% for chronic obstructive pulmonary disease and 36.8% for idiopathic pulmonary fibrosis. Of the patients with pulmonary hypertension by the old definition, 23.9% of chronic obstructive pulmonary disease patients and 18.7% of idiopathic pulmonary fibrosis patients were not classified as pulmonary hypertension by the new definition. Conversely, 15.9% of chronic obstructive pulmonary disease patients and 15.1% of idiopathic pulmonary fibrosis patients who did not meet diagnostic criteria for pulmonary hypertension by the old definition did have pulmonary hypertension by the new definition. Patients in both disease categories had shorter transplant-free waitlist survival in the presence of pulmonary hypertension by both the new and old definitions. There was a trend toward the new definition of pre-capillary pulmonary hypertension better discerning outcomes compared to the old definition of pulmonary hypertension in idiopathic pulmonary fibrosis patients. Most patients with advanced lung disease who are listed for lung transplantation have pulmonary hypertension, but fewer have pre-capillary pulmonary hypertension than pulmonary hypertension by the old definition. Both the old and new definition of precapillary pulmonary hypertension appear to discern outcomes among the two groups of lung disease analyzed, with some evidence to suggest that the new definition performs slightly better in the idiopathic pulmonary fibrosis population.